The Federal Democratic Republic of Ethiopia : Second Review of the Arrangement under the Exogenous Shocks Facility-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Federal Democratic Republic of Ethiopia. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
Ethiopia has successfully implemented policies to reduce inflation and rebuild external reserves. Fiscal policy aims to continue the strong focus on physical and social infrastructure investment while raising the revenue effort. The recent reframing of monetary policy to adopt a reserve money nominal anchor holds out the prospect for the end of financial repression. While the External Shocks Facility-supported program has achieved its objectives of macroeconomic stabilization and a rebuilding of external reserves, much remains to be done to sustain and accelerate growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet